Designing and implementing a digital preservation training needs assessment - Mason, S; Halvarsson, E (iPRES2017, 2017)
This paper describes the design and pilot of a digital preservation training needs assessment at Bodleian Libraries (University of Oxford). The assessment was designed to establish training needs among staff, with the purpose of creating targeted digital preservation training based on gaps identified. Measurements for the assessment were developed around the DigCurV Framework skill descriptors combined with a literature review of other skills frameworks. The measurements were developed into a set of interview questions, which was piloted on nine members of staff from the Oxford University Research Archive (ORA) in the winter of 2016. Findings from the assessment have influenced the design of training modules which frame digital preservation concepts around workflows in the ORA digital repository. The modules take as their starting point the awareness level, knowledge, practical skills, problem solving approaches and preferred learning style of staff within the ORA team.